TAZ inhibits acinar cell differentiation but promotes immature ductal cell proliferation in adult mouse salivary glands. (1st July 2021) - Miyachi, Yosuke; Nishio, Miki; Otani, Junji; Matsumoto, Shinji; Kikuchi, Akira; Mak, Tak Wah; Maehama, Tomohiko; Suzuki, Akira
Abstract: There are currently no treatments for salivary gland diseases, making it vital to understand signaling mechanisms operating in acinar and ductal cells so as to develop regenerative therapies. To date, little work has focused on elucidating the signaling cascades controlling the differentiation of these cell types in adult mammals. To analyze the function of the Hippo‐TAZ/YAP1 pathway in adult mouse salivary glands, we generated ad MOB1DKO mice in which both MOB1A and MOB1B were TAM‐inducibly deleted when the animals were adults. Three weeks after TAM treatment, ad MOB1DKO mice exhibited smaller submandibular glands (SMGs) than controls with a decreased number of acinar cells and an increased number of immature dysplastic ductal cells. The mutants suffered from reduced saliva production accompanied by mild inflammatory cell infiltration and fibrosis in SMGs, similar to the Sjogren's syndrome. MOB1‐deficient acinar cells showed normal proliferation and apoptosis but decreased differentiation, leading to an increase in acinar/ductal bilineage progenitor cells. These changes were TAZ‐dependent but YAP1‐independent. Biochemically, MOB1‐deficient salivary epithelial cells showed activation of the TAZ/YAP1 and β‐catenin in ductal cells, but reduced SOX2 and SOX10 expression in acinar cells. Thus, Hippo‐TAZ signaling is critical for proper ductal and acinar cell differentiation and function i n adult mice. Abstract : We generated adMOB1DKO mice in which both MOB1A and MOB1B were TAM‐inducibly deleted when the animals were adults. Three weeks after TAM treatment, adMOB1DKO mice exhibited smaller submandibular glands (SMGs) than controls with a decreased number of acinar cells and an increased number of immature dysplastic ductal cells.